„Dzisiejsze moralne zwycięstwo jutro można przegrać...” – Rozmawiają Rocco BUTTIGLIONE i Tadeusz STYCZEŃ SDS (tłum. P. Mikulska) - MIKULSKA, Patrycja (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
The present exchange focuses on the main ideas of Tadeusz Styczeń’s paper Der Person gebührt die Liebe [“Love is What the Person Deserves”] presented at the symposium celebrating the tenth anniversary of the International Acade− my of Philosophy in the Prinicpality of Liechtenstein in October 1996. Buttiglione and Styczeń discuss a wide range of metaethical, epistemological, and anthropological issues, focusing on the role of the truth recognized by the subject as the basis for his consitution as rational and free; on the role of the truth as a foundation of social relations, as well as as the source of moral duty. The interlocutors contrast their views with those of David Hume and propose a solution to Hume’s problem of the unity and identity of the subject. They draw on the thought of Plato, Aristotle, St. Gregory of Nyssa, St. Thomas Aquinas, and Karol Wojtyła –John Paul II, and find an unexpected ally in Johann G. Fichte. The dialogue concludes on an ethical note: Styczeń, looking back at the history of Poland, at its failures and triumphs, and especially at the rise of the Solidarity, emphasizes the precariousness of moral victories that cannot be “owned,” but may only be continuously striven for. Summarized by Patrycja Mikulska The exchange between Tadeusz Styczeń, SDS, and Rocco Buttiglione was originally published in German. See: Was ich festgestellt habe, das hält mich fest. Ich bin, wenn ich in der Wahrheit bin oder Ethik als allgemeingültige normative Anthropologie “in der Pille” der Erfahrung. Ein Gespräch über Tadeusz Styczeńs Referat: “Der Person gebührt Liebe…” Rocco Buttiglione – Tadeusz Styczeń, in: Menschenwürde: Metaphysik und Ethik. Jubiläumsband der Internationalen Akademie für Philosophie im Fürstentum Liechtenstein 1986−1996, ed. M. Crespo, Universitätverlag C. Winter, Heidelberg 1998, pp. 207−224. See also: T. S t y c z e ń, Der Person gebührt Liebe. Zum epistemologish triftigen und methodologisch gültigen Ausgangspunkt der Ethik, in: Menschenwürde: Metaphysik und Ethik. Jubiläumsband der Internationalen Akademie für Philosophie im Fürstentum Liechtenstein 1986−1996, pp. 151−193.